Efficacy and safety of influenza vaccination in children with asthma. (April 2012) - Patria, Maria Francesca; Tenconi, Rossana; Esposito, Susanna
The mean global prevalence of asthma among children is approximately 12%, making it the most common chronic disease in children. Influenza infection has been associated with complications such as exacerbations of wheezing and asthma, increased airway hyper-reactivity and hospitalization. Although influenza vaccination is recommended for asthmatic patients by all health authorities, vaccination coverage remains significantly lower than expected and is lowest of all in children. Compliance is affected by the uncertainty of parents and physicians concerning the clinical risk of influenza in asthmatic subjects, the benefits of influenza vaccination in preventing asthma exacerbations and the safety of immunization. The aim of this review is to analyze the rationale for using influenza vaccine, discuss the relationship between influenza and the severity of asthmatic episodes and document the efficacy and safety of influenza vaccination in the pediatric asthmatic population.